The relationship between monetary and non-monetary reward towards job satisfaction among workers - Manimala, Manivanan (2021)
This purpose of the study is to investigate the monetary and non-monetary factor, which influences job satisfaction among employees in private sector. Job satisfaction can be explained as a worker’s evaluation on the level about the work atmosphere, which accomplishes an individual’s requirement. The objective to examine the relationship between monetary and non-monetary towards employee job satisfaction. The study involved 100 respondents from private industrial workers and staffs. The survey method was collected by using questionnaire to the employee who worked in the private companies which located in Klang Valley. This is a quantitative research hence the questionnaire was developed to analyze using “Statistical Package for Sosial”. There are two (2) types of techniques analysis has been adapted which is descriptive analysis and inferential analysis techniques. The purpose is to determine the relationship between independent variables which is rewards (Monetary reward and Non-monetary reward) and dependent variables (Job Satisfaction). This study had recognized that reward is one the factor that influences the job satisfaction. According to the findings, only one independent which is reward was focused. The relationship between job satisfaction and rewards (monetary and non-monetary) is significant. From the researcher point of view, the private sector organization management should not ignore this problems which lead to sudden fluctuation in the rate of satisfaction of the private sector workers and staffs. This study mainly focused an important role to identify variables contributing towards employees’ job satisfaction and also identified few steps to reduce the problem of turnover intention.